Harmonisasi Tata Kelola: Mengurai Benang Kusut Kebijakan Pendidikan Nasional dan Daerah di Era Otonomi - Riza Ummaroch; Dedi Kurniadi; Agus Tinus (Universitas Muhammadiyah Surabaya, 2026)
This research aims to map and analyze the problems of education policy synchronization between the central and regional governments within the framework of regional autonomy in Indonesia. Regulatory misalignment is often a major obstacle to the equitable distribution of national education quality. The research method used is descriptive qualitative with a document study and public policy analysis approach. The research results show that the